A Study of Managing Transportation Route in Food Waste Collection Using Mobile GPS and GIS - Ahmad Umar, Anis Sakinah; Mohd Bukari, Saifullizan (Recent Trends in Civil Engineering and Built Environment, 2023)
Food waste has become an increasing problem in Malaysia. In 2017, Malaysians produce 38,000 tonnes of waste everyday where out of this, around 15,000 tonnes is food waste. Waste collection management that is systematic in the residential area are important because the use of diesel in waste collection trucks can cause greenhouse gases emission that contribute to global warming. The objectives of this study are to determine the route detection using Global Positioning System (GPS) for route mapping and to find out the shortest route for the food waste collection in Pura Kencana and Taman Universiti using Geographic Information System (GIS). The road network in Pura Kencana and Taman Universiti were used in this study. The Mapit GIS application was used for the data collection and shortest route for the food waste collection had been analyzed using Quantum GIS (QGIS). There were three scenarios for the shortest route such as current collection route (R0), different route with same collection point arrangement (R1) and different route with different collection point arrangement (R2). QGIS showed that scenario R2 provided the shortest route and collection time for the overall food waste collection compared to R0 and R1. This proved that QGIS provided the shortest distance and time taken for the food waste collection and at the same time assisted in making wise decision in planning.